Picturing Canada : A History of Canadian Children's Illustrated Books and Publishing - Edwards, Gail (Book collections on Project MUSE., 2010)
An interdisciplinary history, Picturing Canada provides a critical understanding of the changing geographical, historical, and cultural aspects of Canadian identity, as seen through the lens of children's publishing over two centuries.